Creating identity and uniting a nation: the development of the water motif from ancient greek bucolic to early modern English pastoral poetry - Pölzer-Nawroth, Jule F. (2020)
This dissertation aims to perform an intercultural comparison of the history of ancient bucolic (Theocritus, Moschus, Bion and Virgil) and early modern pastoral poetry (e.g. Spenser, Sidney, Marlowe, Ralegh, Barnfield, Milton, Lanyer and Carew) and its influence on the development of cultural and national identity with the help of the water motif. The transience, steadiness and infinity of water has already been connected to almost every aspect of emotionality and sentimentality and offers an apparent supremacy for metaphors and allegories among the five elements. For these reasons water was chosen as a starting point of analysis and this project focuses on its usage, function and relevance in ancient Greek bucolic and early modern English pastoral poetry to demonstrate similarities and differences and to mark precisely developments in genre, form, content and context and their interpretation towards the development of a national identity. The theories used for the analysis and interpretation of the motif and its developments help to situate bucolic and pastoral poetry and its water reference in the right environmental and cultural context and involve pastoral theory, ecocriticism and the theories of collective and cultural memory as well as national identity. Since Pastoral is one of the first genres of poetry composed and printed in the English language, an interesting relationship between the British and the topic of herdsmen poetry appears to be evident. The intriguing question then arises why and how Pastoral became one of the first ‘truly English’ genres, in how far it was influenced by contemporality or ancient literary role models and what its history can offer.